DIRECTIONS FOR ENSURING THE ECONOMIC SECURITY OF ENTERPRISES IN THE CONDITIONS OF MARTIAL ARTS (Development Service Industry Management, 2025)
The article considers the importance of ensuring the economic security of domestic enterprises in conditions of instability and threats from the external environment. The increase in the influence of external risks, in particular geopolitical ones, which negatively affect the financial, energy and labor spheres as a result of the war is noted.Studies indicate that in order to strengthen economic security, it is necessary to implement comprehensive measures that take into account the challenges of modernity, international assistance, reform of the regulatory environment, investments in infrastructure and the creation of a favorable business environment.The development of directions for ensuring business sustainability in conditions of martial law requires both a strategic vision and a tactical approach taking into account the individual characteristics of enterprises. The development of economic security systems should be based on the integration of resources and adaptation to war conditions with the definition of priorities for post-war recovery.Special attention is paid to the analysis of the impact of internal and external threats on economic security. The study substantiates the need to define a system of priorities for the stabilization, recovery and support of business entities in the real sector.Modern instruments provided by the state and international partners are actively used within the framework of the Ukraine Facility initiative. An analysis of the capabilities of this program and the Ukraine Investment Framework project has been conducted. The main areas of support for the country's reconstruction have been identified - in particular, infrastructure, energy, as well as support for small and medium-sized businesses. Key priorities for strengthening security and recovery have been identified.Systemic international assistance combined with the development of internal risk management mechanisms, financial instruments and control over the implementation of decisions allows creating conditions for stabilization.
Keywords: economic security; enterprise; financial security; competitiveness; business; system; components of economic security